The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.14256/jce.2997.2018
|View full text |Cite
|
Sign up to set email alerts
|

A review of factors influencing performance of pervious concrete

Abstract: Pervious concrete is an environment friendly solution for eliminating imperviousness-related drawbacks of conventional concrete. Pervious concrete mixes are predominantly composed of cement, coarse aggregate, and water. The partial or complete elimination of fine aggregate results in porous structure, which influences performance of pervious concrete. This article is aimed at reviewing major factors involved in the design of pervious concrete mixes, namely the compaction, aggregate to cementitious material rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…According to Croush et al [15], the compaction method has a significant impact on strength and permeability. In study [16], the authors recommended using impact methods for compaction Some authors used construction and demolition waste and post-consumer urban waste in pervious concretes [17][18][19]. Zaetan et al [17] investigated the properties of pervious concrete containing recycled concrete-block aggregate and recycled concrete aggregate and found that the replacement of natural aggregate with both recycled aggregates increased compressive strengths and abrasion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…According to Croush et al [15], the compaction method has a significant impact on strength and permeability. In study [16], the authors recommended using impact methods for compaction Some authors used construction and demolition waste and post-consumer urban waste in pervious concretes [17][18][19]. Zaetan et al [17] investigated the properties of pervious concrete containing recycled concrete-block aggregate and recycled concrete aggregate and found that the replacement of natural aggregate with both recycled aggregates increased compressive strengths and abrasion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of 1% and 5% of sand was observed to improve the compressive strength of normal porous blocks from 23-33% and 21-29%, at 7 and 28 days, respectively. In the review study conducted by [26], the authors also concluded the improvement of strength and durability properties due to the addition of fine aggregate that can be due to the enhancement of interfacial bond as also reported by [27] with percentage of fine aggregate addition can be ranged from 5 to 15% to satisfy the application as a sub-base in a rigid pavement. In this experiment, the porous concrete mixture with 5% of sand was then selected for further investigation on the effect of replacing coarse aggregate with different type of plastic waste aggregate as discussed in the next section.…”
Section: Portlandmentioning
confidence: 61%
“…x id = x id + v id (5) where ω is the inertia weight; c 1 and c 2 are the learning factors; and r(x) is the random equation in the range of (0,1). v id should be limited using the following equations:…”
Section: Random Forest (Rf) Modelmentioning
confidence: 99%
“…Permeable concrete is a type of functional concrete that prevents water accumulation on the ground by artificially setting gaps in the concrete, so that the surface water can pass through freely [3,4]. During the preparation of permeable concrete, the interspaces of concrete can be connected by adopting corresponding technical measures [5,6]. Permeable concrete refers to the concrete with internal porosity that is greater than 10%, generally 15% to 30%, and most of the pore diameters are greater than 1 mm, with certain water and air permeability [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%